Targeting chemoattractant chemokine (C–C motif) ligand 2 derived from astrocytes is a promising therapeutic approach in the treatment of neuromyelitis optica spectrum disorders - Wang, Yupeng; Bian, Jiangping; Yao, Mengyuan; Du, Li; Xu, Yun; Chang, Haoxiao; Cong, Hengri; Wei, Yuzhen; Xu, Wangshu; Wang, Huabing; Zhang, Xinghu; Geng, Xingchao; et al. (Frontiers in Immunology, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune astrocytic disease attacked by aquaporin-4 immunoglobulin G (AQP4-IgG) associated with myeloid cell infiltration. Previous studies indicated that the CCR2-positive myeloid cells chemoattractant chemokine (C-C motif) ligand 2 (CCL2) gene is elevated in rat astrocyte cultures stimulated by NMO-IgG. To study the potential function of CCL2 during NMOSD, first, we measured CCL2 levels in paired samples of subject patients and found there were greatly higher CSF-CCL2 levels in NMOSD patients than that in other non-inflammatory neurological diseases (OND) patients. Second, knockdown of the astrocyte-derived CCL2 gene in vitro and in vivo mitigated AQP4-IgG-induced damage efficiently. Furthermore, western blotting, high content screening, qPCR technique, and flow cytometry were conducted to clarify the activation of inflammatory signaling pathways. Interestingly, prevention of CCL2 expression could decrease other inflammatory cytokines released, including IL-6 and IL-1β. Our data suggest that CCL2 involves in the initiation and plays a pivotal role in AQP4-IgG-damaged astrocytes. CCL2 may serve as a promising candidate target for inflammatory disorder therapy, including NMOSD.